Electrical and Optical Properties of Synthesized Composite Material Polyaniline-Ti(IV) Arsenophosphate - Bushra, Rani; Naushad, Mu.; Adnan, Rohana; Shahadat, Mohammad; Ansari, Meenhaz; Ahmed, Anees (Asian Journal of Chemistry, 2015)
Nanocomposite material polyaniline-Ti(IV) arsenophosphate with varying concentration of inorganic precipitate [Ti(IV) arsenophosphate] have been synthesized by employing the sol gel method. Prepared samples were characterized by scanning electron microscopy and transmission electron microscopy. Optical absorption spectra was recorded by using UV-visible absorption spectral techniques. From the analysis of absorption spectra, observed band gap for the different samples was found to be in the range of 3.12 to 3.60 eV. Electrical conducting studies show that conductivity of nanocomposites increases with increase in temperature, which is the observed behaviour of semiconductor materials.